Mother Homer is dead... - Cixous, Hélène,Kamuf, Peggy (Edinburgh University Press, 2018)
The first translation into English of Mother Homer is Dead, written in the immediate aftermath of the death of the Cixous's mother in the 103rd year of her life.
Title from publisher's bibliographic system (viewed on 03 May 2021)
Keywords: Authors; French; Mothers of authors